Removal of pollutants from abattoir wastewater using a pilot-scale bamboo constructed wetland system - Nkeshita, Fidelis C. (Array, 2020)
Wastewater from abattoir sources in urban areas can adversely affect the environment and cause health problems. This research investigated the ability of a bamboo constructed wetland system (BCWS) using Bambusa vulgaris, to treat wastewater from abattoir by removing nutrients and organics. This study adopted pilot scale reactors with bed dimension of 1 m length x 1 m width x 1 m depth to simulate a horizontal sub-surface flow constructed wetland and planted with six strands of bamboo plants. Parameters analyzed include the nutrients (in the form of phosphate and nitrate) and the organics (in the form of Chemical oxygen demand, COD and Biochemical oxygen demand, BOD). The effluent analysis that were carried out within a 28-day retention period showed that there was a very good decrease in the nutrient pollutant parameters; phosphate (99.6 %), nitrate (98.5 %). The organics showed a lesser performance with a 39.3 % removal efficiency for COD and 49.9 % removal efficiency for BOD. Bamboo can be used in a BCWS for low cost green technology in urban areas and can be improved upon by increasing the number of bamboo shoot in order to have a larger root system.